Síntese e caracterização de catalisadores de óxido de cálcio suportado em ferritas magnéticas avaliados na reação de transesterificação etílica - Borges, Diogo Gontijo (2015)
The petroleum crisis associated with global warming and environmental pollution has motivated researchers to investigate more profoundly the feasibility of alternative energy sources. Biofuels have been recently regaining popularity as one of the greatest promises of the high-tech future. Among the different forms of biofuels, biodiesel stands out for being a biodegradable compound, free of sulfur and aromatics. In this context, we developed different routes to synthesize heterogeneous catalysts made of calcium oxide (CaO) supported on magnetic ferrites and evaluated their activity in the transesterification reaction of ethyl. The first synthetic method employed in the preparation of magnetic supports was co-precipitation. The nanometer scale of ferrite particles was achieved by monitoring the flow rate of the reagents and the aging time of the products. The second method involved the usage of the precursor citrate not only due to its low cost but also because it helped in making the synthesis of nanoparticles easier. Furthermore, the wet impregnation method of the respective nitrate was employed in the production of the CaO catalysts which was calcined at 650°C afterwards. The catalysts were characterized by XRD, N2 physisorption, TEM-EDX, SQUID, DTP-CO2 IR and SEM-EDS. The catalysts containing different amounts of CaO were evaluated in the transesterification reaction between methyl acetate and ethanol. The results suggest that a high conversion rate (up to 85%) can be achieved depending on the CaO content on the catalyst. These high conversion rates encouraged us to study the effect of other catalysts on the ethyl transesterification of soybean oil at various reaction times and ethanol/oil molar ratios. Indeed, it was observed that the maximum conversion rate of esters obtained during the ethyl transesterification of soybean oil was higher than 50% in the presence of 50-CaO/ CuFe2O4 catalyst. Moreover, the stability tests showed that these catalysts can be used up to 6 reaction cycles and that Ca2+ leached does not catalyze the homogeneous phase. Therfore, the results suggest that CaO/ MFe2O4 are promising catalysts to replace the base homogeneous catalysts industrialy used for biodiesel production.